Pengembangan Media Pembelajaran Sains Berbasis Digital untuk Mendukung Pembelajaran di Era Masyarakat 5.0 - Lindayani; Nurul Zikri Filina; Dian Erlita; Syah Mohd Hadiid Thaariq; Nurjannah; Ajunda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop digital-based social and natural sciences (IPAS) learning media to support learning in the Society 5.0 era at the elementary school level. The study used the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects were 30 fourth-grade students of Langung State Elementary School in the 2025/2026 academic year. Data collection techniques included observation, interviews, questionnaires, and tests. The feasibility of the media was assessed by material experts and media experts, with the validation score of material experts reaching 87.6% (very feasible) and media experts 91.2% (very feasible). The results showed that digital-based learning media significantly improved student learning outcomes, indicated by an N-Gain score of 0.72 (high category). Student responses to the media showed 89.4% satisfaction (very good category). It was concluded that digital-based IPAS learning media is feasible, effective, and able to support student learning in the Society 5.0 era by integrating technology in the learning process.